Anaphora Resolution on Al-Quran with Indonesian Translation - Arlinda Dwi Ardiyani; Moch Arif Bijaksana; Arief Fatchul Huda (School of Computing, Telkom University, 2020)
Al-Quran is the holy book of Islam, in Al-Quran we often find many cases of anaphora. Anaphora is a pronoun, for example “it” which refers to an object (antecedent) in the previous sentence. Antecedent of a pronoun is very important to understand the Al-Quran. Coreference Resolution with the classification model using the support vector machine method are needed to find out the antecedent. In this research, we use i feature and j feature for the extraction process. Based on the evaluation results, the system is able to find the antecedent of an anaphor with the best accuracy value of 86.36%.